Identification Of Typology Of Green Open Space (RTH) In The Sidoarjo Mud Disaster Area - Moch. Shofwan; V. Rudy Handoko; Arif Darmawan (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The mud disaster that has occurred in Sidoarjo Regency since May 29 2006 was an event of hot gas and mud coming out of the ground with a temperature of 100°C which has occurred in several villages in Sidoarjo Regency. Before the disaster occurred, Porong was a productive area because there were many rice fields, shops, and factories. The three districts affected by the Sidoarjo mudflow, namely Porong District, Tanggulangin District, and Jabon District, previously in 2005, based on satellite imagery, had the form of a spreading Green Open Space (RTH). Based on these problems, it is necessary to identify a typology of Green Open Space in the Sidoarjo Mud Disaster Area. This study discusses the physical typology and function of Green Open Space (RTH) in the sidoarjo mudflow disaster area using the Descriptive-Qualitative Analysis method. Based on the results of the identification of natural Green Open Spaces (RTH) located in the Sidoarjo Mud Disaster Area, only a protected area is found in parts of the Jabon District, namely in Wisata Bahari Tlocor which is located in the Tlocor, Tanjungsari, Kupang, Jabon District with an area of ​​1.40 Ha which is enter the Protected Area.